Pengaruh Instabilitas Makroekonomi Terhadap Non-Performing Financing Perbankan Syariah di Indonesia - Fadilla Muhammad Mahdi (Falah: Jurnal Ekonomi Syariah, 2019)
This study aims to identify the determinants of non-performing financing (NPF) in Islamic banks in Indonesia. The study objects are the Islamic banking industry during the first quarter of 2008 until the third quarter of 2019. The variables in this study are inflation, growth of Gross Domestic Product (PDB), and Bank Indonesia rate. The statistic method used is the Vector Error Correction Model (VECM). The result shows that inflation shock significantly affects the trend of NPF, while others do not give significant effect to NPF of Islamic Banking.